Комплексне детерміноване оцінювання складних ієрархічно-мережевих систем. Частина I. Опис методики - Polishchuk, D. O.; Polishchuk, O. D.; Yadzhak, M. S. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2015)
The main approaches and methods for evaluation of complex systems are analyzed and their advantages and disadvantages are determined. Systems with hierarchical-network structures are described and methods are proposed for their complex deterministic evaluation. Methods of multicriteria and multiparameter local, forecasting, aggregative, and interactive analyses of the state, function quality and interaction of system’s objects on the all hierarchical levels are described. The scheme of interaction is described and it is justified that the proposed methods only in conjunction allow to form objective and grounded conclusions about the quality of a complex system. The proposed methods are illustrated using the analysis of the functioning efficiency of objects of the Ukrainian railway transport system as an example.